POLITIK EKSTRAKTIF DALAM KEBIJAKAN PANGAN Sebuah Perspektif Ekonomi Politik - Abdul Aziz SR (Interaktif : Jurnal Ilmu-Ilmu Sosial, 2018)
This research focused on political-economic perspective of food policy in the era Jokowi-JK governance. The government of Joko Widodo-Jusuf Kalla, from the beginning promised improvements in food self-sufficiency sovereignty. Food sovereignty is contained in the RPJMN 2015-2019 on Food and Agriculture. This study aims to provide an evaluation and analyze from a political-economic perspective to what extent food policy has improved or just the opposite. This research method is descriptive qualitative uses theory of extractive economic political institutions. The results of this study concludes that the government's extractive institutional policy patterns exist in the Jokowi-JK Era in the field of food policy. The food self-sufficiency of the Joko-JK regime has never materialized, partly due to poor planning as well as the lack of seriousness of the government to build self-sufficiency in the food sector.Keywords: Food Policy, Jokowi-JK, Economy Politics Perspective, Extractive Politics